2020
DOI: 10.1093/humrep/dez301
|View full text |Cite|
|
Sign up to set email alerts
|

ICSI does not improve reproductive outcomes in autologous ovarian response cycles with non-male factor subfertility

Abstract: STUDY QUESTION Does the method of fertilisation improve reproductive outcomes in poor ovarian response (POR) cycles when compared to all other ovarian response categories in the absence of male factor subfertility? SUMMARY ANSWER ICSI does not confer any benefit in improving the clinical pregnancy or live birth (LB) outcome in autologous ovarian response cycles in the absence of male factor subfertility when compared to IVF. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 46 publications
0
23
1
Order By: Relevance
“…In studies of unexplained infertility, many have reported higher fertilization rate of ICSI than that of conventional IVF in the presence of normal semen parameters, suggesting that ICSI overcomes undiagnosed male factor subfertility, which was not highlighted in a routine semen analysis (22,23). However, in many studies, higher fertilization rates within the ICSI group did not translate into improved clinical outcomes in the presence of normal sperm parameters (11,24,25). Consistent with previous studies, our study showed that ICSI did not improve the blastocyst formation rate or the chance of having an euploid embryo per allocated oocyte, although a higher fertilization rate per inseminated oocyte was observed in the ICSI group.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of unexplained infertility, many have reported higher fertilization rate of ICSI than that of conventional IVF in the presence of normal semen parameters, suggesting that ICSI overcomes undiagnosed male factor subfertility, which was not highlighted in a routine semen analysis (22,23). However, in many studies, higher fertilization rates within the ICSI group did not translate into improved clinical outcomes in the presence of normal sperm parameters (11,24,25). Consistent with previous studies, our study showed that ICSI did not improve the blastocyst formation rate or the chance of having an euploid embryo per allocated oocyte, although a higher fertilization rate per inseminated oocyte was observed in the ICSI group.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, pointing out that ICSI utilization had more to do with where geographically a clinic was located than it had to do with the etiology of infertility. Furthermore, retrospective analysis of over 20,000 patients found no difference in LBR per cycle between the IVF and ICSI, even when including mild and moderate MF [24]. Please see Table 1.…”
Section: Unselected Patientmentioning
confidence: 97%
“…Possible biases related to the inclusion of retrospective studies in this work and the identification of several confounding factors required very strict bias assessment and advocate for cautious interpretation. Additionally, a high heterogeneity level was observed for the main outcome analysis, which was mainly because of 1 study (6), but also to outliers (6,9,20,22,28). The careful analysis of this study (6) did not allow us to identify some reasons explaining this surprisingly high heterogeneity.…”
Section: Study Limitationsmentioning
confidence: 85%
“…This lack of explanation for heterogeneity prompted further performance of post hoc sensitivity analyses on the basis of a one-by-one exclusion strategy of the studies included in the analysis. This led to the identification of 1 specific study (6), which was responsible for heterogeneity. The exclusion of this study and the 4 outliers did not modify the overall conclusion of the analysis conducted in the remaining 12 studies (121,018 IVF and 219,074 ICSI cycles; RR, 1.08; 95% CI, 1.06-1.09) but led to the dramatic decrease of heterogeneity (I 2 ¼0%).…”
Section: Main Characteristics Of the Available Literaturementioning
confidence: 99%
See 1 more Smart Citation